Rotating ellipsoidal catalytic micro-swimmers via glancing angle evaporation. Issue 21 (27th September 2021) - Kirvin, Alice; Gregory, David; Parnell, Andrew; Campbell, Andrew I.; Ebbens, Stephen
Abstract : A simple one-step glancing angle deposition technique is employed to increase the rotational velocity of anisotropic ellipsoidal micro-swimmers. Abstract : The ability to generate rotation in ellipsoidal catalytic micro swimming devices by catalyst deposition at glancing angles allows reliable access to circling trajectories. This behaviour could enable propulsive ellipsoids to gather cargo and enhance mixing at small scales. Catalytically propelled colloidal rotation has been previously achieved in spherical swimming devices by means of neighbour shadowing during catalyst deposition leading to non-symmetrical coatings. However in this work shadowing effects arise due to the ellipsoid's inherent anisotropy, removing the requirement for a closely packed colloidal crystal monolayer. We use geometric analysis of the catalyst deposition process, and mechanistic understanding to propose a link between the observed trajectories and the catalyst distribution and suggest further routes to improve control of rotation rates.